Sample size calculations made easy using G*Power - Wan Ahmad, Wan Muhamad Amir; Mohd Ibrahim, Mohamad Shafiq; Husein, Adam; Khamis, Mohd Fadhli (Penerbit USM, Universiti Sains Malaysia, 2018)
G*power is a free software that helps researchers to calculate the sample size needed when conducting a research. The importance of sample size calculation is imperative for the knowledge of researchers. Sample size is very important in designing and planning a successful research as it involves time and financial planning. What is best about the G*power is that researchers can plan the real sample size according to their study design, such as minimum sample size for regression analysis with three predictor variables. This technique is commonly used when researchers need a quick decision on: “What is the sample size needed for an analysis?” This brief book illustrates how sample size is calculated based on specific statistical test. The step-by-step and simple discussions through simple presentation and easy-to-understand language used in this book help researchers to understand better about the sample size calculations. http://www.penerbit.usm.my/index.php/buku/261-sample-size-calculations-made-easy-using-g-power